Improving the physical health of people living with mental illness in Australia and New Zealand. (10th October 2018) - Roberts, Russell; Lockett, Helen; Bagnall, Candace; Maylea, Chris; Hopwood, Malcolm
Abstract: People diagnosed with mental illness have relatively poor physical health and die earlier than their counterparts in the general population. People living with mental illness in rural Australia have three times the risk of premature death than the total population. This article reviews recent international, Australian and New Zealand research, identifies the increased risk of early death of people living with mental health issues in rural settings and looks at the need for policy and practice responses. The 'Equally Well' national initiatives are described in Australia and New Zealand, which seek to systematically address this inequity as a matter of priority. Finally, it argues for co‐design and consumer participation in policy development, program implementation and research. Improved understanding of the perspectives and priorities of people with experience of mental illness is vital if change is to be fully realised.